Prawnopodatkowe aspekty agroturystyki - Kapała, Anna (Wydawnictwo Naukowe UAM, 2010)
The aim of this article was an attempt at an evaluation whether and to what degree tax regulations promote agritourism business. Tax regulations referring to this form of agricultural activity were analysed. Italian legal solutions, of long standing, constituted the reference point for the evaluation of Polish regulations. In conclusion the author states that Polish tax solutions concerning agritourism may not be considered less advantageous in comparison to Italian ones, despite the fact that the discussed form of economic activity in Poland does not have the status of the socalled related agricultural activity. The analysed tax systems consider agritourism as economic activity separate from agricultural activity, although they still grant certain privileges. In terms of income tax the Polish legislation, in contrast to the Italian system, allows for a possibility of a complete exemption from taxation for income from agritourism business. Exemptions, tax allowance, tax concessions and other tax relief forms provided for by the Polish law obviously have an effect on the supplementation of income for farmers and on the development of agritourism activity.

Con questo articolo ci si propone di valutare se, e in quale misura, la regolazione fiscale favorisca lo svolgimento dell’attività agrituristica. A tal fine sono state esaminate le norme fiscali riguardanti l’agriturismo. Le soluzioni legislative italiane, aventi una lunga tradizione, costituiscono un punto di riferimento per la valutazione della regolazione polacca. Nella conclusione l’Autrice afferma che le soluzioni fiscali polacche non possono essere considerate meno favorevoli rispetto a quelle italiane, nonostante nell’ordinamento giuridico polacco l’attività agrituristica non abbia lo status dell’attività agricola conessa. Entrambi i sistemi fiscali considerano l’agriturismo come un’attività commerciale distinta da quella agricola, alla quale, tuttavia, riservano alcuni privilegi. Per quanto riguarda, ad esempio, l’imposta sul reddito il legislatore polacco ha previsto, persino, diversamente da quello italiano, nel caso siano soddisfatti determinati criteri, la possibilità di un’esenzione totale dei redditi provenienti dall’attività agrituristica. Indubbiamente, tutti gli esoneri, riduzioni e altre agevolazioni fiscali, previste nel sistema fiscale polacco, favoriscono il sostegno ai redditi degli agricoltori e lo sviluppo dell’attività agrituristica.